Osteoarthritis, Exercise, and Tissue Engineering: A Stimulating Triad for Health Professionals. (2nd May 2019) - Morouço, Pedro; Fernandes, Cristiana; Santos-Rocha, Rita
Abstract : Osteoarthritis (OA) is a degenerative disease, promoted by abnormal chronic mechanical loading over the joint, for instance, due to excessive body mass. Patients frequently report pain, fatigue, and limitations in specific functional daily activities. Regarding the treatment of OA, two nonpharmacological options are available. However, it is not clear which type and intensity of exercise have better outcomes in treatment and how tissue engineering can be a promising field due to the mechanical load implants will suffer. The aims of this work were to investigate (1) the main characteristics, prevalence, and consequences of OA; (2) the exercise prescription guidelines and whether exercise interventions have a positive effect on OA treatment; and (3) the novel improvements on tissue engineering for OA treatment. Both patients and practitioners should be aware that benefits may come from prescribed and supervised exercise. Recent studies have highlighted that an optimal balance between exercise and nutritional income should be widely recommended. Regarding tissue engineering, significant steps towards the development of implants that mimic the native tissue have been taken. Thus, further studies should focus on the impact that exercise (repetitive loading) might have on cartilage regeneration. Finally, suggestions for future research were proposed.